Timber Production in a Working Forest Context - Sonia Delphin; Francisco Escobedo; Chris Demers; Alison E. Adams; Damian C. Adams (EDIS, 2017)
Working forests are private forests managed not just for timber production but also for a host of valuable ecosystem services like providing for recreation, maintaining habitat for wildlife, and maintaining a healthy watershed. Timber production is an essential ecosystem good or service that supports a number of important industries and provides jobs in Florida. This 6-page fact sheet summarizes the results of several studies to help forest landowners and other stakeholders understand how multiple-use management affects both timber production and other ecosystem services. Written by Sonia Delphin, Francisco J. Escobedo, Chris Demers, Alison E. Adams, and Damian C. Adams, and published by the UF School of Forest Resources and Conservation, February 2017.